New frontiers in English literacy education: Preparing critical junior secondary Eastern Indonesia students - Ningsih, Sri Kusuma; Ekawati, Anita Dewi; Setyaningsih, Tri (TLEMC (Teaching and Learning English in Multicultural Contexts), 2025)
This study examines innovative methods for teaching English literacy to junior secondary students in Eastern Indonesia, focusing on critical literacy. Using an ethnopedagogical approach, it investigates the challenges and strategies for implementing critical literacy, the effects on students’ perspectives and cultural identities, and develops tailored teaching models. Data were gathered through classroom observations, interviews with two English teachers and 50 eighth-grade students from two schools, and documents analysis. The findings highlight significant resource disparities between urban and rural areas, requiring creative adaptations of critical literacy methods. Incorporating local contexts into literacy activities strengthened students’ cultural identities and enhanced their engagement with global issues. Successful pedagogical models included bilingual multimodal texts, digital literacy integration, and collaborative project-based learning. The study also identified challenges from traditional teaching methods and an exam-focused culture, suggesting a gradual introduction of critical thinking activities. The findings of the study provide valuable insights for teachers and policymakers on implementing effective English literacy education in diverse, resource-limited settings, underscoring the need for culturally response approaches. Keywords: Critical literacy, English as a foreign language, Eastern Indonesia, ethnopedagogy, student identity